(untitled) (Journal of Geography and Environmental Management, 2018)
The term “ecological tourism” is fairly new and multifaceted. The tourism industry depends on a variety of ecosystem services. In this article, environmental tourism, we understand the organized services, which includes tours of natural, historical and cultural sites, demonstrating the life, traditions and culture of indigenous Kazakh population th dark regions of the southern Kazakhstan region. This article describes some results and prospects of development of ecological tourism in buffer (protection) zone of the oldest and most famous in Kazakhstan Aksu-Zhabagly reserve, spread over an area of 131933,8 ha in the mountainous areas of Western Tien Shan at altitudes from 1000 to 4000 m above sea level. The oldest reserve of Kazakhstan and the first in Central Asia received the status of biosphere reserve and is under the control of UNESCO. In a remote ditch at an altitude of 3000 meters above sea level is another attraction of the reserve is a kind of “art gallery” consisting of a variety of figures carved on dark shiny stones. The basic idea of ecological tourism development near protected areas is to use natural resources, and Aksu-Zhabagly reserve by the local population, 80 years of protecting these resources. Key words: ecology, tourism, protected areas, Park, reserve, technology, recreation, territory, tour, mass, alternative.